Unveiling Historical, Religious, And Philosophical Values of the Indonesia’s Panjunan Red Mosque Via Architectural and Visual Narrative - Kartika, Nyai; Dienaputra, Reiza D; Machdalena, Susi; Nugraha, Awaludin; Suryadimulya, Agus Suherman; Yuliawati, Susi; Sriwardani, Nani (Journal of Islamic Architecture, 2025)
This historical research examines the messages conveyed through the architectural art of an ancient mosque, the Cirebon Panjunan Red Mosque, which was built by Arab descendants living in Java in 1480 AD. In Indonesia, the acculturation between Islamic culture and traditional values resulted in the uniqueness of mosques' architectural buildings and ornaments. In addition to being a place of worship, mosques became an art form rich in symbols, representing historical, religious, and philosophical values. This qualitative research with historical methods seeks to investigate the visual narrative in the ancient mosque by implementing a series of historical research stages, including heuristics, criticism, and data interpretation. As pictures convey a narrative as well as words, visual narrative can be used to discover the values of the past. The results of the research have unveiled messages of history and culture regarding Islam's development during the Cirebon sultanate. In addition, the history of the Panjunan Red Mosque was described. Hopefully, this research can contribute to new knowledge on the past Islamic development in Indonesia and the wisdom of peaceful acculturation.